K’asba’e T’oh: sustaining the intergenerational transmission of Tāłtān - Morris, Kāshā Julie Anne (2017)
The Tahltan language is endangered and at a critical juncture because there are now fewer than 30 fluent speakers. The Tahltan Nation is working to change this by creating many different opportunities for language learning, focusing on programming, documentation, and professional development and training. One way that our language is being revitalized is through immersion programs for young children. Using ‘Tahltan Voiceability’ as the overarching methodology, this study reports on the language nest model as an immersion method of Indigenous language revitalization in Tahltan communities in northern British Columbia. Parents, language mentors, and administrators shared their perspectives and experiences regarding the way in which K’asba’e T’oh (the Dease Lake Language Nest) began in Tātl’ah (Dease Lake), how things are progressing, and what motivated and continues to motivate people to be involved. Through an analysis of these conversations, I share esdahūhedech (their tellings) and report on emerging themes. With this immersion setting in place, there is hope that this program will create speakers, inspire others to learn our language, and be part of increasing the proficiency of language learners, thereby moving our language out of the endangered status. This study is part of a growing body of research in Canada studying language nests to promote the intergenerational transmission of Indigenous languages. Graduate